2019
DOI: 10.1186/s13584-019-0332-6
|View full text |Cite
|
Sign up to set email alerts
|

Digital recording and documentation of endoscopic procedures: physicians’ practice and perspectives

Abstract: Background In recent years, it has become increasingly prevalent internationally to record and archive digital recordings of endoscopic procedures. This emerging documentation tool raises weighty educational, ethical and legal issues – which are viewed as both deterrents and incentives to its adoption. We conducted a survey study aimed at evaluating the use of DRD in endoscopic procedures, to examine physicians’ support of this practice and to map the considerations weighed by physicians when deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that in some regions, such as Israel, despite having high access to DRD equipment, the actual recording rates remain low among doctors (4). Factors limiting the widespread adoption of endoscopic video recording include (i) doctors' concern about the potential risk of lawsuits, (ii) privacy concerns from both the patients and professionals, and (iii) lack of a clearly defined legal framework for video recording in medical practice (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that in some regions, such as Israel, despite having high access to DRD equipment, the actual recording rates remain low among doctors (4). Factors limiting the widespread adoption of endoscopic video recording include (i) doctors' concern about the potential risk of lawsuits, (ii) privacy concerns from both the patients and professionals, and (iii) lack of a clearly defined legal framework for video recording in medical practice (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The described benefits of video recordings include (i) improving quality, efficiency, and safety of care, (ii) improving clinical skills of healthcare providers, (iii) medical education, and (iv) improved patient follow-ups (3,4,(6)(7)(8). Rural hospitals lack access to resources to support the purchase of new, often expensive digitized medical equipment or DRD devices.…”
Section: Introductionmentioning
confidence: 99%
“…Potential risks to patients’ rights have been examined and organized into six categories: informed consent policies, informed consent procedures, recorded medical errors, secondary use of recordings, collateral patient information, and public trust issues ( 11 ). An additional concern may be the medicolegal aspects in the event of a complication ( 12 ). The authors note that their hospital consent form included consent for videotaping for training and education purposes.…”
mentioning
confidence: 99%